2022
DOI: 10.1097/md.0000000000029375
|View full text |Cite
|
Sign up to set email alerts
|

Impact of phase angle and sarcopenia estimated by bioimpedance analysis on clinical prognosis in patients undergoing hemodialysis

Abstract: Bioimpedance analysis (BIA) has been widely used in the evaluation of body composition in patients undergoing maintenance hemodialysis. We conducted this study to evaluate impact of phase angle (PA) and sarcopenia measured by BIA on clinical prognosis in these patients.This longitudinal retrospective study enrolled patients who underwent hemodialysis between January 2016 and March 2019. The patients were stratified into higher (> 4°) and lower ( 4.0°) PA groups. Sarcopenia was defined when the appendicular ske… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Among patients with HD, Kim et al [22] reported that the risk of CVD events was three times higher in those who had low muscle mass than in the control group. Conversely, another study on patients with HD found that appendicular skeletal muscle mass, which was measured by bioimpedance analysis, was not a significant risk factor for major adverse cardiovascular events [23]. Furthermore, ratio, albumin, uric acid, FTI (when LTI being considered as an independent variable), LTI (when FTI being considered as an independent variable).…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Among patients with HD, Kim et al [22] reported that the risk of CVD events was three times higher in those who had low muscle mass than in the control group. Conversely, another study on patients with HD found that appendicular skeletal muscle mass, which was measured by bioimpedance analysis, was not a significant risk factor for major adverse cardiovascular events [23]. Furthermore, ratio, albumin, uric acid, FTI (when LTI being considered as an independent variable), LTI (when FTI being considered as an independent variable).…”
Section: Discussionmentioning
confidence: 94%
“…Among patients with HD, Kim et al [22] reported that the risk of CVD events was three times higher in those who had low muscle mass than in the control group. Conversely, another study on patients with HD found that appendicular skeletal muscle mass, which was measured by bioimpedance analysis, was not a significant risk factor for major adverse cardiovascular events [23]. Furthermore, although other reports showed more consistent associations between loss of muscle strength and mortality [13, 2427], the importance of low muscle mass as an independent predictor of mortality in dialysis populations remains controversial [22, 23].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In critical illness states, a weakened membrane integrity, a reduced cell count, and a modified hydration status lead to a reduced PhA. These situations correlate with an increased mortality rate and the length of the hospital stay [ 52 , 53 , 54 ]. While many studies have been conducted on healthy subjects, obese individuals, the elderly population, and hemodialysis patients, we need more data on metabolic surgery diabetes remission patients [ 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%